Realignment Matrix of Digital Campus Master Plan based on Digital Transformation Maturity Assessment - Yanuar Firdaus Arie Wibowo; Dawam Dwi Jatmiko Suwawi; Amarilis Putri Yanuarifiani; Widia Febriyani (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
The previous research that created a framework for evaluating the level of digital maturity and digital transformation in higher education is a valuable resource for universities when revising their Digital Campus Master Plan (DCMP). DCMP is an integral part of a university's life cycle and is derived from their Strategic Plan. The strategic planning within DCMP should be reviewed regularly and adapted to the latest changes in digital maturity and digital transformation within the university. A university's level of digital maturity is a measure of their readiness to incorporate digital technology and information technology into their campus. The goal of a digital transformation in universities is not only to implement technology but to also develop new strategies and methods of working that positively impact the university experience for students (digital journey). The digital transformation maturity assessment is crucial in helping universities align or restructure their DCMP or Information Technology Master Plan (ITMP). The outcome of this research is a matrix that will guide the digital transformation planning team in realigning or redeveloping the DCMP.